Prenatal stress is a vulnerability factor for altered morphology and biological activity of microglia cells - Ślusarczyk, Joanna; Trojan, Ewa; Głombik, Katarzyna; Budziszewska, Bogusława; Kubera, Marta; Lasoń, Władysław; Popiołek-Barczyk, Katarzyna; Mika, Joanna; Wędzony, Krzysztof; Basta-Kaim, Agnieszka (Frontiers in Cellular Neuroscience, 2015)
Several lines of evidence suggest that the dysregulation of the immune system is an important factor in the development of depression. Microglia are the resident macrophages of the central nervous system and a key player in innate immunity of the brain. We hypothesized that prenatal stress (an animal model of depression) as a priming factor could affect microglial cells and might lead to depressive-like disturbances in adult male rat offspring. We investigated the behavioral changes (sucrose preference test, Porsolt test), the expression of C1q and CD40 mRNA and the level of microglia (Iba1 positive) in 3 month old control and prenatally stressed male offspring rats. In addition, we characterized the morphological and biochemical parameters of potentially harmful (NO, iNOS, IL-1β, IL-18, IL-6, TNF-α, CCL2, CXCL12, CCR2, CXCR4) and beneficial (IGF-1, BDNF) phenotypes in cultures of microglia obtained from the cortices of 1-2 days old control and prenatally stressed pups. The adult prenatally stressed rats showed behavioral (anhedonic- and depression-like) disturbances, enhanced expression of microglial activation markers and an increased number of Iba1-immunopositive cells in the hippocampus and frontal cortex. The morphology of glia was altered in cultures from prenatally stressed rats, as demonstrated by immunofluorescence microscopy. Moreover, in these cultures, we observed enhanced expression of CD40 and MHC II and release of pro-inflammatory cytokines, including IL-1β, IL-18, TNF-α and IL-6. Prenatal stress significantly up-regulated levels of the chemokines CCL2, CXCL12 and altered expression of their receptors, CCR2 and CXCR4 while IGF-1 production was suppressed in cultures of microglia from prenatally stressed rats. Our results suggest that prenatal stress may lead to excessive microglia activation and contribute to the behavioral changes observed in depression in adulthood.